Лев и собачка: рассказы / Л. Н. Толстой - Толстой Лев Николаевич (Внеклассное чтение, 2007)
Экземпляры: ф.17 (10.11.2008) / Инвентарный номер: 40601 / Цена: 28.27 / Авт.знак: Т 53 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1